2023
DOI: 10.1021/jacs.3c02041
|View full text |Cite
|
Sign up to set email alerts
|

Expandable Li Percolation Network: The Effects of Site Distortion in Cation-Disordered Rock-Salt Cathode Material

Abstract: Cation-disordered rock-salt (DRX) materials receive intensive attention as a new class of cathode candidates for high-capacity lithium-ion batteries (LIBs). Unlike traditional layered cathode materials, DRX materials have a three-dimensional (3D) percolation network for Li+ transportation. The disordered structure poses a grand challenge to a thorough understanding of the percolation network due to its multiscale complexity. In this work, we introduce the large supercell modeling for DRX material Li1.16Ti0.37N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…It has been reported that the activation of tetrahedral vacancies and the distribution of the overall percolation network are related to the cation disorder and short-range ordering arrangement in the material. 18,24 As illustrated in Fig. 3d, the smaller radius of Si 4+ possesses a stronger polarization ability than Ti 4+ and Li + .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been reported that the activation of tetrahedral vacancies and the distribution of the overall percolation network are related to the cation disorder and short-range ordering arrangement in the material. 18,24 As illustrated in Fig. 3d, the smaller radius of Si 4+ possesses a stronger polarization ability than Ti 4+ and Li + .…”
Section: Resultsmentioning
confidence: 91%
“…8–12 Several transition metals such as Mn, Ti, V, and Cr have been utilized to synthesize DRXs with capacities of up to 300 mA h g −1 . 13–17 Transition metal cation mixing, 11,18 short-range ordered structure analysis, 19–22 and the Li + migration mechanism 23–26 are highly researched to activate the high capacity and improve the rate performance of DRXs. Recently, Konuma et al reported a “near dimensionally invariable” material Li 8/7 Ti 2/7 V 4/7 O 2 , which was encapsulated in Li 6 PS 5 Cl-based ASSBs using a PEEK mold and achieved a capacity of 300 mA h g −1 at a high operating pressure of 200 MPa and a current of 0.2 C (60 mA g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the variation in the distortion of the BO 6 (B = Ti3, Ta3) that is very distant from the mobile Li ion is much smaller than the variations in the distortion of the BO 6 (B = Ti1, Ti2, Ta1, Ta2), indicating that the change in SOJT distortion of the BO 6 was strongly correlated with Li-ion diffusion. In a recent study on cation-disordered rock-salt materials with TiO 6 as cathode candidates for high-capacity LIBs, the specific influence of TiO 6 distortion on Li percolation was elucidated in detail . The distortion of BO 6 assisting Li-ion diffusion may be a common feature in solid electrolytes and electrode active materials for LIBs that contain d 0 B ions.…”
Section: Resultsmentioning
confidence: 99%
“…The valuable effect of Ni doping was to add the bonus of increased charge–discharge capacity to the excellent cycling stability of the layered rock-salt type. This strategy must be valuable not only for TiO 2 -based anode materials but also metal-oxide-based cathode materials with a cation-disordered rock-salt structure, , Ni-rich layered structure, and phosphate olivine structure …”
Section: Results and Discussionmentioning
confidence: 99%